Improvement of collapsible soil behavior of a lateritic soil using rice husk ash - Fagundes, Luiza P. [UNESP]; Yacoub, Jhaber D. [UNESP]; Lima, Andrey C. [UNESP]; Nakatsuchi, Flávia R. [UNESP]; Lollo, José A. [UNESP]; Akasaki, Jorge L. [UNESP]; Tashima, Mauro M. [UNESP] (Trans Tech Publications, 2016)
Great areas of Brazil present lateritic soils, such as the northeast and the south. Some of these soils have, as main characteristic, instable structures that can present considerable volumetric deformation in the presence of water. This behavior, also named collapse, is responsible for several problems on the building construction such as cracks and fractures that can damage the safety of structures. The aim of this paper is to assess the possibility of improvement of collapsible behavior of a lateritic soil using rice husk ash (RHA). A previous characterization of soil and RHA was performed in order to assess the combined effect of soil/RHA. The results are so promising, showing a new alternative to reduce the collapsible behavior of soils using an environmental friendly technology.
Keywords: Collapsible behavior; Lateritic soil; Rice husk ash